Extensive Resection for Treatment of Locally Advanced Primary Mucinous Adenocarcinoma Arising From Fistula-in-Ano - Jordan Au; Francis M. Hulme-Moir; Andrew Herd; Mathew A. Kozman (Annals of Coloproctology, 2021)
We report a case of a 66-year-old male who presented with a locally advanced primary mucinous adenocarcinoma arising from a fistula-in-ano. The presentation was typical for perianal sepsis and fistula-in-ano with anal pain and chronic discharge. Initial treatments with fistula debridement and seton were performed. Subsequent review of histology revealed underlying adenocarcinoma, while magnetic resonance imaging (MRI) showed local invasion into the prostate. The patient received neoadjuvant chemoradiotherapy followed by pelvic exenteration to maximize the chance of achieving cure. Features of this case are discussed together with its implications, including treatment guidelines and typical MRI findings.